2013
DOI: 10.1016/j.rser.2013.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the environmental Kuznets curve in a global economy

Abstract: Abstract:The present study deals with an empirical investigation between CO 2 emissions, energy intensity, economic growth and globalization using annual data over the period of 1970-2010 for Turkish economy. We applied unit root test and cointegration approach in the presence of structural breaks. The direction of causality between the variables is investigated by applying the VECM Granger causality approach. Our results confirmed the existence of cointegration between the series. The empirical evidence repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
122
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(151 citation statements)
references
References 47 publications
21
122
2
6
Order By: Relevance
“…The presence of the EKC in Pakistan is consistent with Nasir and Rehman (2011), Shahbaz et al (2012), Ahmed and Long (2012), Ahmed et al (2015), and Ali (2015). For the Turkish economy, our results are similar to Shahbaz et al (2013b), and Elgin and Öztunalı (2014), but dissimilar with Halicioglu (2009), Ozturk and Acaravci (2010), and Kaplan et al (2011) who supported the absence of EKC for Turkey.…”
Section: The Ekc Hypothesis Analysiscontrasting
confidence: 67%
See 1 more Smart Citation
“…The presence of the EKC in Pakistan is consistent with Nasir and Rehman (2011), Shahbaz et al (2012), Ahmed and Long (2012), Ahmed et al (2015), and Ali (2015). For the Turkish economy, our results are similar to Shahbaz et al (2013b), and Elgin and Öztunalı (2014), but dissimilar with Halicioglu (2009), Ozturk and Acaravci (2010), and Kaplan et al (2011) who supported the absence of EKC for Turkey.…”
Section: The Ekc Hypothesis Analysiscontrasting
confidence: 67%
“…Shahbaz et al (2013b) revisited the causality between energy consumption, economic growth, and CO 2 emissions for the Turkish economy and found the presence of feedback effect between energy consumption and economic growth, economic growth and CO 2 emissions, and energy consumption and CO 2 emissions. Ghosh (2009) investigated the causal relationship between income and CO 2 emissions by incorporating other variables into the emissions function and found no causality between income and CO 2 emissions for India.…”
Section: Studies On the Nexus Between Energy Consumption Co 2 Emissimentioning
confidence: 99%
“…The first group of studies focuses on the economic growth and pollution nexus (Heil and Selden 1999;Halicioglu 2009;Soytas and Sari 2009;Shahbaz et al 2013). Akbostanci et al (2009) have investigated the relationship between income and environmental quality in Turkey for the years from 1968 to 2003 and the results concluded that there is an increasing relationship between CO 2 and income in the long run.…”
mentioning
confidence: 99%
“…This would ensure an economic growth that would be delinked with environmental impact 24,25 . What follows is a discussion on the methods that India can adopt to outlast the dangers of climate change and global warming.…”
Section: Emissions Global Warming and The Indian Economymentioning
confidence: 99%